Importance of coverage and quality for impact of nutrition interventions delivered through an existing health programme in Bangladesh - Nguyen, Phuong Hong; Frongillo, Edward A.; Sanghvi, Tina; Kim, Sunny S.; Alayon, Silvia; Tran, Lan Mai; Mahmud, Zeba; Aktar, Bachera; Menon, Purnima (Wiley, 2018)
Understanding implementation of interventions is critical to illuminate if, how, and why the interventions achieve impact. Alive & Thrive integrated a nutrition intervention into an existing maternal, neonatal, and child health (MNCH) programme in Bangladesh, documenting improvements in women's micronutrient supplement intake and dietary diversity. Here, we examined how well the nutrition intervention was implemented and which elements of implementation explained intervention impact.